Borys Bałter — zapomniany „szestidiesiatnik” - Sałajczyk, Janina (Przegląd Rusycystyczny, 2011)
BORYS BAŁTER — ZAPOMNIANY «SZESTIDIESIATNIK» Streszczenie Wstępna część artykułu przedstawia główne fakty biografii Borysa Bałtera. Następnie omówiono zawartość problemową i aspekty formalne najważniejszego jego utworu — powieści Do widzenia, chłopcy! (1962). Podkreślono jej związek z nurtem prozy psychologicznej i autobiografizm oraz liryzm narracji. BORIS BALTER — FORGOTTEN “SHESTIDIESATNIK» Summary The introductory part of this paper presents major facts from Boris Balter`s biography. Then were discussed problems of content and formal aspects of his most important literary work — novel Goodbye, boys! (1962). There were stressed the relations to the psychological and autobiographical prose as well as the lyricism of narration.